Pengembangan E-modul Berbasis Literasi Sains Tema Ayo Siaga Bencana untuk Melatih Kemandirian Belajar Siswa SMP - Hilda Kristina; Mudmainah Vitasari; Annisa Novianti Taufik (PendIPA Journal of Science Education, 2022)
This research was based on the constraints found in the field about the science learning process in junior high schools. Learning activities oriented to scientific literacy and student independence have not been carried out optimally. Independent learning can be implemented by training it through e-modules based on scientific literacy. This study aims to detail the efficiency level of e-modules based on scientific literacy with the theme let's prepare for disasters to train the learning independence of junior high school students. The method used is Research & Development with the ADDIE model, namely the stages of analysis, design, development, implementation and evaluation. At the implementation stage, the results of the validity of the scientific literacy-based e-module with the theme let's be prepared for disaster to train junior high school students' learning independence showed that based on validation by material experts, the percentage score was 93.7% in the "Very Valid" category, validation by teaching materials experts obtained a percentage value. 89% in the "Very Valid" category and validation by expert educators obtained a percentage of 85.79% in the "Very Valid" category. The results of the efficiency level of e-module products reached a percentage value of 87.16% in the "Very Efficient" category.